PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI PARTISIPASI DALAM PENGELOLAAN HUTAN DESA DURIAN RAMBUN - Sri Rahma; Nurfitri Martaliah; Puji Wahyuli (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2021)
This study aims to provide an analysis of women's participation in forest management through the Village Forest mechanism in Durian Rambun Village, Merangin Regency, Jambi Province. Village Forest is one of the social forestry mechanisms aimed at creating the welfare of communities that coexist with forests. This research is qualitative research with descriptive methods to explain phenomena in detail. Data collection methods are carried out by interviews, observations and literature studies. The results showed that women's participation in forest management through Village Forests is necessary, women and forests are entities that cannot be released. Through participation in forest management, Durian Rambun village women are economically empowered by utilizing forest land to produce and produce coffee products. Management is carried out sustainably so that forest sustainability still occurs in accordance with the principles of social forestry management.